Semiotics of Oral Literature: A Kinesics Perspective. - Ajayi, Omofolabo Apinke (Obafemi Awolowo University, 2018)
This thesis attempts a kinesics analysis of oral literature - an art form transmitted through both the verbal and non-verbal communication (nvc) channels. Kinesics is concerned with body motions (e.g. gestures and dance), as related to non verbal aspects of interpersonal communication. Underlying the kinesics perspective is semiotics, a study of the verbal as well as the nvc signs and their meanings. The semiotic analysis, therefore, investigates the dynamics of kinesics communication in oral literature and the corresponding signification system between its verbal and non-verbal channels. The oral literature of the Yoruba people is used as a case-study.